PENGOLAHAN KUNINGAN MENJADI EMBELLISHMENT PADA PRODUK FASHION - Sinuraya, Silvia Thessalonica; Siagian, Marissa Cory Agustina; Sekar, Ahda Yunia (ATRAT: Jurnal Seni Rupa, 2021)
Brass Is a mixture of copper with zinc which can produce a gold-like luster. Brass handicraft products can also be processed into fashion products for embellishment. Orchid is a very popular ornamental plant, with a wide variety of colors and shapes. One of them is the black orchid. By combining these aspects, black orchids with unique and rare types can make fashion products with embellishment from brass material into items that look more luxurious with their image. With this explanation, there is a potential for brass metal to be processed into modular embellishment in fashion products, especially with the black orchid model to be applied to fashion products. Using qualitative methods in order to produce valid data with exploration methods are also used by knowing the proper processing and composition to get good beads. The results of this research aim to develop and create the latest innovations in embellishment beading from brass metal, especially etsa and ukir techniques so that they can be applied to fashion products.Keywords: Brass, Embellishment, Black Orchid, Fashion Products------------------------------------------------------------------------------------------Kuningan merupakan campuran tembaga dengan seng yang dapat menghasilkan kilau seperti emas. Produk kerajinan kuningan juga dapat diolah menjadi produk fashion sebagai embellishment. Anggrek merupakan tanaman hias yang sangat populer, dengan memiliki berbagai macam warna dan bentuk. Salah satunya adalah anggrek hitam. Dengan menggabungkan aspek ini, anggrek dengan jenis yang unik dan langka dapat membuat produk fashion dengan embellishment dari bahan kuningan menjadi barang yang lebih terlihat mewah dengan image-nya. Dengan keteragan tersebut, adanya potensi pada logam kuningan untuk diolah menjadi modular embellishment pada produk fashion, khususnya dengan model anggrek hitam untuk diaplikasikan pada produk fashion. Dengan menggunakan metode kualitatif agar menghasilkan data yang valid. Metode eksplorasi juga digunakan dengan cara mengetahui pengolahan dan komposisi yang tepat untuk mendapatkan beads yang baik. Hasil penelitian ini bertujuan untuk mengembangkan dan membuat inovasi terbaru dalam embellishment beading dari bahan logam, khususnya teknik etsa dan ukir agar dapat di aplikasikan kepada produk fashion.Kata Kunci: Kuningan, Embellishment, Anggrek Hitam, Produk Fashion